Inequality, power and policy change: How Chile moved towards greater political transparency - Bettina Schorr (United Nations Research Institute for Social Development (UNRISD), 2020)
Policy and legislative mechanisms that enforce transparency and accountability, and place limits on politicians' behaviour, are useful tools for addressing political corruption, which constitutes a problem of particular gravity in Latin America. A number of scandals have recently come to light, such as the case involving the Brazilian company Odebrecht, showing the scale of political corruption in the region. While the subject of political transparency is at the top of many domestic political agendas, however, comprehensive regulation to prevent political corruption through mechanisms of transparency and accountability is still rather scarce. It would seem that curbing the opportunities for collusion between politics and business is particularly difficult in Latin America's unequal societies, because this would require that those holding power and potentially benefiting from political corruption must adopt and implement rules that would restrain such behaviours. Thus, one of the most important questions when dealing with issues of political transparency is how to push regulators to regulate themselves. While Latin America on average scores poorly regarding the adoption and implementation of political transparency rules, Chile's performance is an outlier. Since 2015, reforms have been under way in the country to improve political transparency. This paper analyses the political process that led to the relatively progressive political transparency governance scheme in Chile. It identifies the mechanisms and factors that shaped the political process in such a way that political reforms for greater transparency were enacted.
Keywords: 330; Civil society; political corruption; governance; political process; public policy